Advanced modulation coding schemes for an optical transceiver systems–based OWC communication channel model - Hazem M. El-Hageen; Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
This paper examines advanced modulation coding schemes for an optical transceiver systems–based optical wireless communication (OWC) channel model. These modulation techniquesinclude On-Off keying and return to zero (RZ)/non–return to zero (NRZ) coding. The signal power level against time and frequency spectral variations are measured. The max. Q factor and min. bit error rate (BER) are estimated and clarified for each modulation code scheme by using an optisystem simulation model. Transmission bit rates of up to 40 Gb/s can be achieved for possible distances up to 500 km with acceptable Q factor. The received power and max. Q factor are measured and clarified with OWC distance variations. The On-Off keying modulation code scheme resulted in better performance than the other modulation code schemes did.